Pelatihan Pembuatan Tes Uraian Berbasis Hard Skills Matematik bagi Guru-Guru SD Swasta IT Darussalam - Nurdiana Siregar (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
The ability of teachers to carry out learning evaluations including making tests based on mathematical hard skills is still low, not all teachers have studied the assessment guidebooks in elementary schools, descriptive tests can identify understanding of mathematical concepts and measure students' problem solving abilities. The solution offered is the provision of training in making descriptive tests based on hard skills mathematics for teachers of SDS IT Darussalam, Deli Tua District. This training method is in the form of lectures, workshops, question and answer, practice, and exercises. The understanding ability of the trainees is 85%, while the results of making essay tests based on mathematical hard skills are 82%. It can be stated that the competence of teachers in making hard skills-based mathematical test descriptions can increase.